2014
DOI: 10.18632/oncotarget.3083
|View full text |Cite
|
Sign up to set email alerts
|

An update on the LIM and SH3 domain protein 1 (LASP1): a versatile structural, signaling, and biomarker protein

Abstract: The gene encoding the LIM and SH3 domain protein (LASP1) was cloned two decades ago from a cDNA library of breast cancer metastases. As the first protein of a class comprising one N-terminal LIM and one C-terminal SH3 domain, LASP1 founded a new LIM-protein subfamily of the nebulin group. Since its discovery LASP1 proved to be an extremely versatile protein because of its exceptional structure allowing interaction with various binding partners, its ubiquitous expression in normal tissues, albeit with distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 107 publications
4
105
2
Order By: Relevance
“…LIM and SH3 domain protein (LASP1) a dynamic protein involved in cell structure, physiological processes and cell signaling, is significantly expressed in various malignancies and associated with tumor aggressiveness [40] and is reported to be an independent prognostic factor in patient’s survival for gastric cancer [41] and hepatocellular carcinoma [42]. We also found that LASP1 was associated with poor overall survival in our cohort.…”
Section: Discussionsupporting
confidence: 63%
“…LIM and SH3 domain protein (LASP1) a dynamic protein involved in cell structure, physiological processes and cell signaling, is significantly expressed in various malignancies and associated with tumor aggressiveness [40] and is reported to be an independent prognostic factor in patient’s survival for gastric cancer [41] and hepatocellular carcinoma [42]. We also found that LASP1 was associated with poor overall survival in our cohort.…”
Section: Discussionsupporting
confidence: 63%
“…As LASP1 is overexpressed in several cancer entities [14] it was tempting to speculate that the protein might also be involved in the development and progression of melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…11-13 LASP1 encodes a LIM motif at its N-terminus and an src homology 3 (SH3) domain at its C-terminus. In LASP1, SH3 domain functions in protein-protein interactions 28,29 and LASP1 acts as an actin-binding protein and overexpression of LASP1 enhances cancer cell proliferation and invasion. 13,28,30 Our present data showed that LASP1 is a putative candidate of these antitumor miRNA regulation, suggesting that LASP1 is a key molecule for cancer cell aggressiveness.…”
Section: Discussionmentioning
confidence: 99%